2020
DOI: 10.1177/2055207620958528
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a novel unified healthcare model to compare practice patterns between telemedicine and in-person visits

Abstract: Objective Telemedicine practice has been shown to vary from clinical guidelines. Variations in practice patterns may be caused by disruptions in the continuity of care between traditional and telemedicine providers. This study compares virtual and in-person visits in Stanford’s ClickWell Care (CWC) – where patients see the same provider for both visit modalities. Methods Clinical data for two years of patient encounters at CWC from January 2015–2017 (5772 visits) were obtained through Stanford STRIDE. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…There is no similar study that examines the conditions that exist in Sweden, although there are a couple of international studies. A study, which investigated twenty various diagnoses, showed that there was no difference in prescriptions, labs and images ordered by online doctors and physicians met in person [30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is no similar study that examines the conditions that exist in Sweden, although there are a couple of international studies. A study, which investigated twenty various diagnoses, showed that there was no difference in prescriptions, labs and images ordered by online doctors and physicians met in person [30].…”
Section: Discussionmentioning
confidence: 99%
“…The study examined antibiotic prescribing based on ATC-codes (Anatomical Therapeutic Chemical . The usage of ATC-codes for identifying antibiotic prescriptions and ICD-10-diagnosis codes are not unique and were commonly employed in many similar studies [27,28,29,30,32]. Infection diagnoses were selected in order to determine if there is a difference in antibiotic prescription patterns between private digital care providers and traditional primary healthcare.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations